PENGARUH MOTIVASI, PERSEPSI, DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SIRUP MEREK VALUE PLUS - Siti Rohmah Maulinda; Rintar Agus Simatupang (Jurnal Riset Manajemen dan Bisnis, 2010)
This study examines the effect of consumer’s motivations,perceptions and attitudes toward their purchasing decisions on Plus-Value branded Syrup. This study uses survey methods. The sampels used in this study are 125 respondents. The results show that consumer’s motivation and attitudes positively influence on their purchasing decisions. Meanwhile the perception has no effect on consumer’s purchasing decisions.Keywords: motivation, perception, attitude, purchasing decision.